2021
DOI: 10.1007/s42978-021-00108-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Performance of Alpine Skiers with Inertial Motion Units: Practical and Methodological Considerations

Abstract: Although reliable feedback is crucial to improving the performance of competitive alpine skiers, the coach's eye may not be sensitive enough to detect small, but highly significant “mistakes”. Monitoring of the performance of alpine ski racers by inertial motion units (IMU) has proven to be of value in this context and here we summarize practical and methodological aspects of this approach. Methodologically, the IMUs employed should combine high sampling frequencies with minimal signal drift. The sensors shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In alpine skiing, IMUs can offer a number of advantages that go beyond the limitations of traditional or laboratory methods [43][44][45][46][47][48][49]: compact and lightweight, easily portable and positionable, capable of wireless operation, and with the ability to capture a substantial amount of data (i.e., several runs), instantaneous data acquisition, and the optimization of data collection due to automatic synchronization among all the built-in sensors. However, to the best of our knowledge, no research has been conducted yet to evaluate MV through IMUs in the domain of alpine skiing, nor has it been evaluated regarding how the characteristics of the terrain (flatter vs. steeper slopes) and course setting (gate offset: i.e., turned vs. straighter courses) influence skier MV.…”
Section: Introductionmentioning
confidence: 99%
“…In alpine skiing, IMUs can offer a number of advantages that go beyond the limitations of traditional or laboratory methods [43][44][45][46][47][48][49]: compact and lightweight, easily portable and positionable, capable of wireless operation, and with the ability to capture a substantial amount of data (i.e., several runs), instantaneous data acquisition, and the optimization of data collection due to automatic synchronization among all the built-in sensors. However, to the best of our knowledge, no research has been conducted yet to evaluate MV through IMUs in the domain of alpine skiing, nor has it been evaluated regarding how the characteristics of the terrain (flatter vs. steeper slopes) and course setting (gate offset: i.e., turned vs. straighter courses) influence skier MV.…”
Section: Introductionmentioning
confidence: 99%
“…Afterword, MARG sensors were introduced in controlling Unmanned Aerial Vehicle (UAV) and capturing its motion through providing precise attitude information to the control system [8]. In sports, attitude information can be utilized for instance in estimating the performance and the characteristics of skiers [9]. In addition, MARG sensors can be used in measuring countermovement jump performance metrics in elite basketballers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in alpine skiing, inertial measurement units (IMUs), global positioning systems (GPSs), pressure-sensitive insoles, and surface electromyography (sEMG) have been applied to analyse skiers' kinematics, kinetics, and muscle activation patterns ( 5 23 ). An overview of their application and the resulting methodological consequences for further use has recently been addressed in two review articles ( 24 , 25 ). Furthermore, it has been suggested that sensor-based approaches may provide feedback to enhance sports performance or prevent injury in general, not just for competitive athletes ( 26 ).…”
Section: Introductionmentioning
confidence: 99%